Pojęcie efektywności i konkurencyjność gospodarek rynkowych - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The problem of competitiveness of economies is broadly described in foreign and Polish literature. It is viewed from different perspectives, including, among others, analysis of factors of competitiveness and rankings created. The effectiveness and efficiency of the economy is in turn much less frequently undertaken. There are difficulties in defining and measuring effectiveness.Competitiveness is closely linked to the problem of effectiveness and efficiency. Attempting to simultaneously describe these concepts can greatly expand the area of analysis. The issue of efficiency occupies a leading position among the general socioeconomic problems. The future of any economy largely depends on the possibility to raise its effectiveness. There is currently no fully comprehensive theory of efficiency, although there are already some of its components.
Keywords: konkurencyjność; efektywność; system gospodarczy